Severe Nodulocystic Acne Induced by Mercury-Containing Skin-Whitening Cream: A Case Report and Call for Public Awareness - Sami Alsuwaidan; Khalid Nabil Nagshabandi; Abdulmajeed Alajlan (Karger Publishers, 2024)
Introduction: Skin-whitening products, often containing mercury, are used worldwide for cosmetic purposes but pose significant health risks. Mercury, a melanotoxin, can cause severe dermatological, renal, and neurological complications. Case Presentation: We report the case of a 27-year-old woman who developed severe nodulocystic acne due to chronic use of a mercury-containing skin-whitening cream. Treatment with isotretinoin and prednisolone led to significant improvement within 3 months. Conclusion: This case underscores the need for public awareness and stricter regulatory actions to prevent mercury-related health hazards from skin-whitening products.